Increased Social Support Mitigates the Negative Impact of Food Insecurity on Antiretroviral Adherence Among Postpartum Women in Western Kenya (P04-126-19). (13th June 2019) - Wang, Mira; Miller, Josh; Collins, Shalean; Santoso, Marianne; Wekesa, Pauline; Onono, Maricianah; Gandhi, Monica; Young, Sera
Abstract: Objectives: Antiretroviral (ARV) adherence is a strong predictor of improved health outcomes and treatment effectiveness among persons living with HIV. Food insecurity and low social support are have been demonstrated to predict reported nonadherence among pregnant women, but the relationship has not been evaluated using an objective indicator of adherence. Therefore, we explored the impacts of social support and food insecurity on ARV adherence using ARV drug concentrations in hair among postpartum Kenyan women living with HIV. Methods: Hair samples were collected from 83 HIV + women, a subset from an observational pregnancy cohort study (NCT02974972), on Efavirenz ( n  = 58) and Nevirapine ( n  = 25)-based ARVs at nine months postpartum. Hair ARV concentrations were log transformed to approximate a normal distribution. Food insecurity [Individual Food Insecurity Access Scale (IFIAS, 0–27)], social support (Perceived Social Support Scale, 0–40), and quality of life (Short Form 8 Health Survey, 0–40] were recalled for the prior month. These covariables, along with sociodemographic characteristics, were included in a multivariable linear regression model ( P  < 0.2) and eliminated using a backward stepwise approach ( P  < 0.1). Results: Mean IFIAS score was 10.0 (± 5.2). Lower food insecurity and greater quality of life were significantly associated with higher hair ARV concentrations. Each point increase in IFIAS and decrease in quality of life was associated with a 13.4% decrease (95%CI: −0.23, −0.05) and 15.7% decrease (95%CI: 0.06, 0.23) in hair levels, respectively. Social support was not significantly associated with ARV adherence in bivariate analysis, but did buffer against the negative impacts of food insecurity on ARV adherence in the final multivariable model (Figure 1). Conclusions: This study demonstrates that low food insecurity is significantly associated with higher ARV adherence among postpartum women using an objective biomarker, and that social support can buffer the negative effect of food insecurity on adherence. Interventions addressing these modifiable barriers to ARV adherence should be explored to improve adherence among HIV + postpartum women. Funding Sources: The study was supported by the National Institute of Mental Health and the National Institute of Allergy and Infectious Diseases. Supporting Tables, Images and/or Graphs: